Pola Komunikasi Masyarakat Adat Kasepuhan Cicarucub Dalam Kegiatan Adat Ngaseuk - Rosy Destiana; Dini Valdiani; Yogaprasta Adi Nugraha (Jurnal Penelitian Sosial Ilmu Komunikasi, 2023)
Ngaseuk is the activity of growing rice in huma (dry land) using aseuk (to lift the taper). Ngaseuk is a traditional activity carried out by the Kasepuhan community to start ngamumule pare activities (maintaining rice). This activity is special because it is an early activity in the life cycle of the kasepuhan community. Because the interest of people, not only tourists but also academics, is the basic reason for this. This study was conducted to identify the communication patterns that exist in the Kasepuhan Cicarucub through traditional ngaseuk activities. The researcher dissected based on communication activities, the interaction of symbols, and components of ritual communication that occur during traditional activities. This study used a qualitative method with an ethnographic approach to focus on the traditional communication process of ngaseuk. The data collection technique used was in-depth interviews, observation, and document studies. The results showed that the Kasepuhan Cicarucub community still adhered to customary rules which included ngamumule pare (maintaining rice) as a life cycle that the Kasepuhan community had to live, which was inherited from their ancestors. The ngaseuk activity which is an escort for the life cycle of the Kasepuhan community has a deep meaning of communication with God, nature, and fellow human beings to produce a unique and distinctive communication pattern. So that it finds that the communication pattern that occurs in the Kasepuhan Cicarucub community in Ngaseuk traditional activities forms a transcedental communication pattern because the communication between indigenous peoples and something supernatural.